Lucifer. The complete first season [videorecording (DVD)] - Alejandro, Kevin, 1976-; Estevez, Scarlett, 2007-; Harris, Rachael, 1968- (Warner Bros., 2016)
Bored and unhappy as the Lord of Hell, Lucifer has resigned his throne and retired to the City of Angels, where he is indulging in wine, women, and song. When a beautiful pop star is brutally murdered before his eyes, he feels something awaken deep within him, for the first time in ten billion years. Is he actually capable of feelings for a human being? The very thought disturbs him, as well as his best friend and confidante, Mazikeen, a fierce demon in the form of a beautiful young woman.